2008
DOI: 10.1182/blood-2007-06-096784
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling in classic Hodgkin lymphoma

Abstract: IntroductionMature microRNAs (miRNAs) are naturally occurring small noncoding RNAs that act as negative regulators of gene expression through messenger RNA interference. These molecules were described for the first time in 1993 by Ambros and colleagues in Caenorhabditis elegans (Lee et al 1 ), and to date, hundreds of miRNAs have been identified in other species, including viruses. 2,3 miRNAs are encoded by intronic or intergenic DNA regions, primarily as large molecules that can exceed 1 Kb, and are cleaved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 49 publications
9
142
0
Order By: Relevance
“…miR-27a, mapped to chromosome 19p13, which was gained in seven of ten primary cHL cases in the present study, was shown to be one of the most strongly upregulated microRNA in cHL cell lines. 46 Collectively, the data from the present study show that array CGH of primary HRS cells enables the detection of new genomic imbalances and the delineation of known ones. Furthermore, our findings suggest that genomic aberrations in HRS cells may contribute to the typical cHL-specific phenotype with constitutive expression of several signaling pathways via gene dosage effects.…”
Section: Several Components Of Constitutively Activated Signaling Patmentioning
confidence: 95%
“…miR-27a, mapped to chromosome 19p13, which was gained in seven of ten primary cHL cases in the present study, was shown to be one of the most strongly upregulated microRNA in cHL cell lines. 46 Collectively, the data from the present study show that array CGH of primary HRS cells enables the detection of new genomic imbalances and the delineation of known ones. Furthermore, our findings suggest that genomic aberrations in HRS cells may contribute to the typical cHL-specific phenotype with constitutive expression of several signaling pathways via gene dosage effects.…”
Section: Several Components Of Constitutively Activated Signaling Patmentioning
confidence: 95%
“…111 On the more clinical end of the research spectrum, profiling of microRNAs in many other kinds of cancers is proceeding rapidly, with recent examples from cervical, prostate, pancreatic, and germ cell tumors, among many others. 92,94,[113][114][115][116][117][118] Characteristic microRNA patterns offer new information that could yield advances in tumor classification and prognosis determination, although the clinical validation of such efforts will require some time.…”
Section: Microrna In Disease Statesmentioning
confidence: 99%
“…Indeed, MIR21 was the only consistently up-regulated miRNA in a study that profiled 540 clinical samples from cancer patients . Overexpression of this miRNA has been documented in both Hodgkin and non-Hodgkin lymphoma (Lawrie et al, 2007;Navarro et al, 2008). MIR21 has been shown to target many tumour suppressor genes including tropomyosin 1 (TPM1), programmed cell death 4 (PDCD4) and maspin (SERPINB5) in breast cancer and lymphoma (Zhu et al, 2008;Schramedei et al, 2011), PTEN in hepatocellular cancer and NK/T cell lymphoma (Meng et al, 2007;Yamanaka et al, 2009), tissue inhibitor of metalloproteinase-3 (TIMP3) in glioma (Gabriely et al, 2008), tumour suppressor genes ANP32A and SMAR-CA4 in B-cell lymphoma (Schramedei et al, 2011), and multiple components of the TP53, transforming growth factor-b (TGFB1), and mitochondrial apoptosis tumour-suppressive pathways (Papagiannakopoulos et al, 2008).…”
Section: Mir21mentioning
confidence: 99%